2005
DOI: 10.1136/emj.2004.022665
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and healthcare burden of illegal drug use among emergency department patients

Abstract: Objectives: Illegal drug use is common in emergency department (ED) patients, but previous prevalence studies have relied upon approaches that may underestimate the true extent of the problem. The aim of this study was to examine illegal drug use in a typical adult ED. Methods: We employed an independent researcher to prospectively and anonymously interview patients attending an inner city adult ED throughout all 168 hours of a typical week. Additional information collected from the treating clinician indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Studies of patients visiting emergency departments (ED) have found that 10–20% report recent use of illicit drugs , much higher than the general population, and diagnoses of drug dependence are common among frequent ED users . Frequent ED users are particularly likely to use drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients visiting emergency departments (ED) have found that 10–20% report recent use of illicit drugs , much higher than the general population, and diagnoses of drug dependence are common among frequent ED users . Frequent ED users are particularly likely to use drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Drug-related conditions form a major part of the workload of some hospital emergency departments in the United Kingdom and elsewhere ( 1 – 3 , 6 ). We aimed to identify emerging trends in hospital admission for SSTIs and vascular disease arising from drug use and, specifically, where these may have occurred after injection of the femoral vein.…”
mentioning
confidence: 99%
“…16 ED presentations of alcohol and OS, including prescription drugs abuse can be a burden on the ED staff and are often associated with significantly more psychiatric and physical health comorbidity. [17][18][19] In the context of Qatar and its unique legal and sociodemographic makeup, measuring ED presentations of alcohol and OS abuse is a good starting point for scoping the extent of the problem and informing public health policy in designing interventions to manage this problem. This study presents the first such comprehensive data on individuals presenting to all the major EDs of Qatar with primary diagnosis of alcohol and drug misuse.…”
Section: Open Accessmentioning
confidence: 99%